(untitled) (Research, Society and Development, 2020)
The objective was to evaluate composition bromatological aspects of silage with 20% elephant grass and 80% cupuaçu cake at different storage times. The experiment was carried out in the Bromatology sector of the Federal University of Acre (UFAC), Rio Branco-Acre, in a completely randomized design (DIC), with five treatments and four repetitions (T1 = 7 days; T2 = 14 days; T3 = 21 days; T4 = 28 days and T5 = 35 days). Twenty experimental polyvinyl chloride (PVC) silos with a capacity of 2 kg were used and hydrogen potential (pH), dry matter (DM), crude protein (PB), mineral material (MM), ether extract (EE), fiber were evaluated acid detergent (FDA), neutral detergent fiber (NDF), hemicellulose (HEM), lignin (LIG), dry matter losses (PMS), gases (PG) and effluents (PE). The data were subjected to analysis of variance and means compared by the Tukey test (P<0.05), using the statistical program SISVAR, version 2012. The results regarding the hydrogen potential (pH) differed statistically (P<0.05). MS, PB, MM, EE, and NDT showed significant differences (P<0.05) between treatments, with emphasis on 35 days of storage, which showed better content of FDA, HEM and LIG. The levels of HEM, gas losses (PG) and effluents (PE) differed statistically (P<0.05). It was concluded that elephant grass silages with cupuaçu cake in the studied bromatological composition showed bromatological composition with losses of dry matter, effluents and gases at acceptable levels when the storage period is longer than 28 days.